Mosquito repellent property of "Ylang-Ylang" (Cananga odorata) essential oil in urea-formaldehyde microencapsulated cotton fabric - Reyes, Eriko Lois B.; Menor, Marvin D.; Munsayac, Michelle G.; Notario, John Bryan P.; Ogaco, Gianne Henriette A.; Perez, Jueliand Peter A.; Ramos, Eleanor Kay S.; Tengco, Susan Geraldine C.; Rio, Phyllis C.; Hilario, Allan L. (2020)
Common mosquito-borne diseases in the Philippines include dengue, Chikungunya, Japanese encephalitis, malaria, and filariasis. Mosquito repellents are effective protective measures against mosquito bites and microencapsulation of essential oils to fabric is currently an emerging trend for mosquito repellency. Accordingly, ?ylang-ylang? (Cananga odorata) is a fast-growing tree endemic to the Philippines and found to have mosquito repellent properties. This study aimed to determine the mosquito repellency of microencapsulated ylang-ylang oil applied to cotton fabrics. The difference in the mosquito repellent property between untreated and treated fabrics in different concentrations of microencapsulated ylang-ylang oil was tested. The prepared microcapsules containing 10 mL and 2.5 mL ylang-ylang oil were applied to separate cotton fabrics using a bath exhaustion method. The fabrics were examined using a scanning electron microscope and showed irregularly shaped and rough-walled microcapsules with sizes ranging 50?100 μm. The fabrics were then tested for mosquito repellency using the World Health Organization (WHO) cone test in five replicates. An untreated fabric served as negative control. The test of significance used the one-way analysis of variance (ANOVA), and the p-value was set at p < 0.05. The fabrics treated with 10 mL and 2.5 mL microcapsules showed increasing rates of mosquito repellency from 80 ± 10% to 88 ± 8.37% and from 64 ± 5.48% to 82 ± 8.37%, respectively (p < 0.05). The mosquito percent repellency showed a significantly higher % repellency in treated than the untreated fabric (p < 0.05). The fabric with microcapsules containing 10 mL of ylang-ylang oil has greater mosquito repellency than that of 2.5 mL (p < 0.05). In conclusion, this study suggests the potential of urea-formaldehyde microencapsulation as an effective method in making cotton fabrics with mosquito repellent properties using ylang-ylang (Cananga odorata) essential oil.
Includes bibliographical references (pages 1035-1037)
Keywords: Essential oil; Microencapsulation; Mosquito repellent; Ylang-Ylang.